Wide hybridization and introgression of anthracnose resistance in the background of local land races of rajmash (Phaseolus vulgaris L.) - KUMAR, SANJEEV; SAHA, ARCHANA JOSHI; KOTWAL, NEERAJ; GUPTA, RUCKU (The Indian Journal of Agricultural Sciences, 2026)
An attempt of wide hybridization was made between Phaseolus vulgaris cultivated lines × Phaseolus vulgaris wild lines, Phaseolus vulgairs ×  Phaseolus coccineus, Phaseolus vulgaris ×  Phaseolus acutifolius and Phaseolus vulgairs ×  Phaseolus lunatus under controlled conditions to widen the genetic base of rajmash at School of Biotechnology, SKUAST J during kharif 2021 and 2022. RILs of both intra and inter specific hybrids of F4 and F5 generations were evaluated for anthracnose and agronomical traits at Regional Horticulture Research Station Bhaderwah, of SKUAST J during kharif 2023 and 2024. The success of hybrid establishment and their comprehensive development was up to 18.28% in intra-specific hybrids with accessions of secondary gene pool, 3.94–9.04% with tertiary gene pool and only 0.5% with quarterly gene pool. However, with mentor pollinated the achievement rate of intra-specific hybrids was 16.84%. On the basis of pooled mean performance RIL14 of Bhaderwah local ×  Poonch Local in F4 and F5 generations showed maximum seed yield (15.56 g/plant) along with moderate resistance against anthracnose. Similarly, RIL11of mentor pollinated inter-specific hybrid in F4 and F5 generations showed higher seed yield (29.79g/plant) along with resistance against anthracnose. The application of wild species of rajmash i.e., P. coccineus, P. acutifolius and Phaseolus lunatus for the improvement of rajmash was just initiated and success rate is very less in India and remains limited. Promising RILs of both intra and inter-specific hybrids may be further evaluated for stability in performance for varietal development programme in the background of local land races of rajmash of Union Territory of Jammu & Kashmir.